KITAB ALALA: KATALISATOR PEMBENTUKAN KARAKTER RELIGIUS PADA SISWA DI MI DARUSSALAM JOMBANG: Analisis Implementasi Nilai Kitab Kuning dalam Pembentukan Akhlak Siswa” - Zainiyah, Madinatul (MIDA : Jurnal Pendidikan Dasar Islam, 2025)
This study explores the correlation between the instruction of Kitab Alala and the development of students' religious character at MI Darussalam Jombang. Employing a quantitative correlational approach, the research involved a purposive sample of 30 sixth-grade students. Data were collected through a structured questionnaire based on indicators of Kitab Alala instruction and dimensions of religious character. The Spearman test yielded a significance value of 0.002, indicating a statistically meaningful relationship between the two variables. Furthermore, the coefficient of determination (0.341) suggests that Kitab Alala instruction contributes 34% to the formation of students’ religious character. These findings highlight the continued relevance of classical Islamic texts in instilling moral and spiritual values. This research contributes to the development of character education models rooted in traditional Islamic literature, offering contextual and applicable approaches for Islamic elementary education.